Factor structure and psychometric properties of the Resilience Scale in a chronic musculoskeletal pain sample. - Ruiz-Párraga, Gema Teresa; López-Martínez, Alicia Eva; Gómez-Pérez, Lydia (Elsevier, 2012)
The concept of resilience is receiving increasing attention in the field of chronic pain. It has been shown to play a protective role in patients with osteoarthritis, fibromyalgia, and rheumatoid arthritis. Despite this, no resilience measurements have been validated in chronic pain populations. The Resilience Scale (RS) is a well-known instrument that has been used to assess resilience in studies conducted in the general population. When used in chronic pain samples, this scale presented the highest internal consistency compared to other resilience scales. The main aim of this study was to provide data on the factor structure, reliability and validity of the RS in a sample of chronic musculoskeletal pain patients (n = 300). Factor analyses revealed a single-factor solution of 18 items (RS-18) which accounted for 52.43% of the total variance of this scale. The RS-18 shows good reliability (internal consistency and stability) and construct validity. This scale has the advantage of excluding items closely related to functional disability and impairment. Furthermore, the RS-18 significantly correlated with several pain-related variables (i.e., catastrophizing, pain acceptance, active and passive pain coping, anxiety, depression, pain-related anxiety, disability, functioning, impairment, and pain intensity). Clinicians and researchers are thus provided with a valid and reliable instrument to assess resilience in chronic pain populations.
Keywords: Dolor crónico - Aspectos psicológicos; Psicometría; Resilience scale; Chronic pain; Measurement; Reliability; Factor structure; Validity